Oral dysphagia due to dental resin allergy: A rare case report - Yangzhou Huang; Zhouhui Wu; Yong Chen; Daobin Zhu; Lihua Fu (Acta Oto-Laryngologica Case Reports)
The primary complaints of dysphagia and tongue enlargement are often initially evaluated by otolaryngologists, although these conditions may sometimes be related to diseases managed by other specialties. However, such diseases may be urgent, develop rapidly, and require emergency treatment. Herein, we report a rare case of a 72-year-old man who presented to the otolaryngology department with primary complaints of dysphagia and tongue enlargement 5 h. Furthermore, we could only temporarily administer symptomatic treatment with dexamethasone. Finally, a dental resin skin prick test was performed. The purpose of this case report was to raise awareness clinicians regarding the symptoms of oral dysphagia, the timeliness of diagnosis, the search for etiology, and comprehensive management.